Combining sterile insects with disseminator devices of fungus spores to control Drosophila suzukii under confined conditions - Amanda Ayala; Sergio Campos; Roberto Méndez; Jorge Juan; Dina Orozco-Davila; Víctor Gutiérrez; Salvador Flores; Marysol Aceituno-Medina; Emilio Hernández; Pablo Montoya (Discover Animals)
Abstract Here we present the results of the concurrent use of the sterile insect technique (SIT) plus fungal spore disseminator devices (DD) to control Drosophila suzukii Matsumura populations under laboratory conditions. Our study includes tests to determine the sterile: fertile ratio to induce sterility in the target population, as well as the conditions for packing and shipping the irradiated pupa to destination. We found that a 40:1 sterile: fertile male ratio was consistent inducing an 80% of sterility, and that hypoxia (24 h) was the most influential factor on the adult emergence and adult flier percentage parameters, which decreased significantly per se and combined with irradiation and temperature, revealing that irradiated D. suzukii pupae are highly sensitive to hypoxia and uncontrolled temperature during shipping conditions. Regarding the concurrent use of SIT plus DD of fungus spores, we found that males infected with entomopathogenic fungi successfully transmit fungal spores (75.56 ± 6.27% for Isaria javanica and 78.98 ± 6.02% for Metarhizium brunneum), the transmission to females affects their fecundity (mx) over time. We also observed that the treatment of SIT plus DD of fungal spores significantly reduced at least of 50% the offspring of the pest population compared to SIT alone and the control treatment (no SIT or fungus). These results suggest that both strategies can be successfully integrated in the control of D. suzukii populations under confinement conditions.